2015
DOI: 10.1016/j.expneurol.2014.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal glucocorticoid-induced hypomyelination, gliosis, and neurologic deficits are dose-dependent, preparation-specific, and reversible

Abstract: Postnatal glucocorticoids (GCs) are widely used in the prevention of chronic lung disease in premature infants. Their pharmacologic use is associated with neurodevelopmental delay and cerebral palsy. However, the effect of GC dose and preparation (dexamethasone versus betamethasone) on short and long-term neurological outcomes remains undetermined, and the mechanisms of GC-induced brain injury are unclear. We hypothesized that postnatal GC would induce hypomyelination and motor impairment in a preparation- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Such genes have the expression so strongly correlated with that of many other genes that their forced alteration triggers unbearable perturbations of major functional pathways. In tens of previous papers on a large variety of cells and tissues from humans [21,22] and animal (e.g., mouse [10,11,29,38], rat [13,30,39], rabbit [56], dog, chicken embryo [12]) models of human diseases, we proved that major functional pathways remodel in disease, with certain genes being promoted to command positions. We know that a gene is critical for a particular phenotype when its expression is strongly controlled by the homeostatic mechanisms, making it resistant to the small environmental fluctuations and thus very stably expressed across biological replicas.…”
Section: Discussionmentioning
confidence: 82%
“…Such genes have the expression so strongly correlated with that of many other genes that their forced alteration triggers unbearable perturbations of major functional pathways. In tens of previous papers on a large variety of cells and tissues from humans [21,22] and animal (e.g., mouse [10,11,29,38], rat [13,30,39], rabbit [56], dog, chicken embryo [12]) models of human diseases, we proved that major functional pathways remodel in disease, with certain genes being promoted to command positions. We know that a gene is critical for a particular phenotype when its expression is strongly controlled by the homeostatic mechanisms, making it resistant to the small environmental fluctuations and thus very stably expressed across biological replicas.…”
Section: Discussionmentioning
confidence: 82%
“…However, the use of immunosuppressant steroids dexamethasone, or mineralocorticoids have been reported to show side effects as well as impaired neurodevelopment (Halliday et al, 2003). Animal studies have shown that glucocorticoids, especially repeated administration of dexamethasone, adversely affect myelination of the developing brain (Zia et al, 2014). Despite mixed reports of improvement in myelination in models of lipopolysaccharide-induced perinatal brain injury (Pang et al, 2012) it is now widely accepted that the risks of cerebellar and WM damage by glucocorticoids during critical periods of brain development may outweigh its benefits on immunosuppression.…”
Section: Strategies For Improving Protection and Repairmentioning
confidence: 99%
“…However, repeated antenatal glucocorticoid courses can cause adverse effects on fetal growth and cerebral cortical maturation 7 without further reducing the incidence of PIVH 44 . Postnatal glucocorticoids (dexamethasone or betamethasone) cause a preparation- and dose-dependent reversible reduction in oligodendrocyte proliferation and maturation, reduction in myelination, induced astrogliosis, and impaired motor functions evaluated on postnatal days 14 and 21 in rabbit pups 45 , see also 46 . Here, morphological data indicate that ACTH 1-24 microinjected 12 h after collagenase in PN 2 alleviated the impact of PIVH in rats.…”
Section: Discussionmentioning
confidence: 99%